DEVELOPMENT OF STUDENTS’ CULTURAL COMPETENCIES BASED ON AN INTEGRATIVE APPROACH (E Global Congress, 2023)
This article is dedicated to the development of students’ cultural competence based on an integrative approach. Approaches to the development of cultural competence to students were considered.